Paneth cells, antimicrobial peptides and the regulation of the intestinal microbiota - Salzman, Nita (Henry Stewart Talks, 2011)
The human microbiome, 16S ribosomal RNA, Physiological roles of the intestinal microbiota, Mammalian mucosal surfaces, Paneth cells, Intestinal antimicrobial peptides, The defensins: animal models, Defensins, regulation of the microbiota and implications for intestinal homeostasis, Paneth cells and the regulation of intestinal homeostasis, Diseases associated with Paneth cell abnormalities
Updated at 2017/02/27